Design of Heyzine Flipbook Based Arabic E-Module as an Alternative Teaching Material for Basic’s Level - Agung Heru Setiadi; Mahbub Humaidi Aziz; Moh. Ainin; Abdul Wahab Rosyidi; Bima Fandi Asy'arie; Zainul Fuat (Universitas Islam Negeri Jurai Siwo Lampung, 2024)
One innovation in learning Arabic is using digital platforms such as Heyzine Flipbook (HF), which has been proven to increase student motivation. This research aims to develop and analyze the product design of the Arabic Learning E-module via HF. The method used is “Research & Development” (R&D) with the ADDIE model. The focus of this article is at MIN 2 East Lampung. Several applications (Canva, Quizizz, and Wordwall) are supported to create product designs for Arabic learning materials. Then, the product feasibility test involved six validators, namely material and language experts, who got 83.9%, learning media experts got 84.7%, and learning design experts got 83.5%. In the small group test, the score was 87.5%, while in the significant group test, the score was 67.3%. In terms of effectiveness, the application of this product shows very good results, with an average increase in student grades of 57.0%. In this way, all students achieve completeness after the Arabic e-module development product via HF can be implemented optimally.